Teoretična in terminološka izhodišča izseljenstva ter poznavanje tematike izseljenstva med slovenskimi učenci in dijaki - Ilc Klun, Mojca (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2014)
The first part of the paper deals with basic theoretical and terminological aspects of emigration, including migration theories and theoretical discourse of migration terminology. The second part is focused on key findings of empirical research among 687 Slovenian pupils of nine schools, which show the knowledge of emigration terminology among the youth.
Keywords: demografija; demography; dijaki; družbena geografija; human geography; human migration; izseljenci; migracije; pouk; Slovenia; Slovenija; strokovni jezik; terminologija; terminology; učenci